Development of a rapid method for the quantification of methamidophos and chlorpyrifos by Thin Layer Chromatography in soils using image processing - Gonzales-Condori, Elvis Gilmar (2022)
20th LACCEI International Multi-Conference forEngineering, Education, and Technology: “Education, Research and Leadership in Post-pandemic Engineering: Resilient, Inclusive and Sustainable Actions”